Egypt 5 Years After the Revolution: A Political Gratifications Study of the Motives for Viewing Television News and Political Programs That Predict Political Attitudes. (June 2018) - Al-Kandari, Ali A.; Hasanen, Mohammed M.
This study employs the uses and gratifications perspective to examine the motives that led a sample of 466 university students in Egypt to view television news and political programs and whether those motives and the frequency of exposure to media predict political efficacy, support for democracy, and political cynicism. The outcomes revealed that motives for viewing were Support in Discussions, Watchdog on Government, Reinforcement, Opinion Formation, Information, and the Free Marketplace of Information. Although Support in Discussions predicted political efficacy and the Free Marketplace of Information negatively predicted it, levels of prediction were not powerful. Support for democracy was weakly predicted by Information, Support in Discussions, the Free Marketplace of Information, and Watchdog on Government. Political cynicism was not predicted by any media variables. The motives for media use are discussed in relation to the political psyche of Egyptians and the political conditions affecting Egypt after the revolution.